Thursday

July 31, 2014

July 31, 2014

Posted by **agnes** on Sunday, January 23, 2011 at 9:53pm.

- math -
**Reiny**, Sunday, January 23, 2011 at 10:23pmfrom the 2nd

y = 2x-3 after dividing by 2

sub into the first

3x - 6(2x-3) = 5

3x - 12 + 18 = 5

I bet you can finish it from here

**Related Questions**

Substitution Method-Plz help - Use the Substitution method to solve the system ...

Linear Equations - Can you please help solve this equation using the ...

Math - Solve the system by using the substitution method. y= 3/4x - 4 -x + 2y= -...

math - Solve the following system using the substitution method: 2x + 4y = 5 x...

math - Solve the following system using the substitution method: y = 3x - 9 y...

Math - I still don't know how to directly solve this problem. Can someone guide ...

algebra - What is the solution of the system? Solve the system of equations ...

math - Solve using the substitution method. If the system has no solution or an ...

math - Solve using the substitution method. Show your work. If the system has no...

algebra - Solve the following system using the substitution method: 6x - 2y = -4...